Peran Karakteristik Kewirausahaan Islam dan Modal Sosial Islam Untuk Resiliensi UMKM - Muhammad Halim Maimun; Hafidh Munawir (Benefit: Jurnal Manajemen dan Bisnis, 2022)
Micro, Small and Medium Enterprises (MSMEs) play an important role in socio-economic development in Indonesia. However, MSMEs are more vulnerable to changes that result in losses, because MSMEs have limited resources. The Covid-19 pandemic is a serious challenge for SME operations. The resilience of their MSMEs is a priority during the pandemic. This study was conducted to explore the factors that affect the resilience of SMEs in Solo Raya. Using a quantitative approach, hypothesis testing uses Partial Least Square (PLS). The results obtained that the characteristics of Islamic entrepreneurship and Islamic social capital together have a significant effect on the resilience of MSMEs, especially in the context of Covid-19. The results of the study highlight that improving the characteristics of Islamic entrepreneurship should be prioritized to increase the resilience of SMEs